A Semiotic Analysis of Avatar Movie (2009) - S, Mugil Karthick (Journal of Advanced Research in Journalism & Mass Communication, 2023)
Filmmakers have to ensure that their movies provide a sense of realism to the audience. However intense the dialogues are, the visual representation of objects, actors and everything else in a frame plays a key role in strengthening the movie's reality among the audiences. With Mise-en-scène the composition, lighting, costume, props, and any other object on frame can carry a meaning to the audience. This study semiotically analysis the movie Avatar (2009) by understanding the role of mise-en-scène in effective narration. The movie’s mise-en-scène is analysed for presence of signifiers that contribute to the narration of the film. These signifiers are semiotically analysed using Ferdinand de Saussure’s theory of semiotics. This research paper uses a descriptive qualitative method of analysis. The relationship between the signifier and the signified has established the effective use of sign through mise-en-scène. Through the mise-en-scène the film makers have semiotically carried concepts of imperialism, corporate greed, importance of ecology thus, Mise-en-scène has also been useful in providing realistic visuals of the imaginary world of Pandora.